The characteristics of pods and seeds of liana species Derris trifoliata and their relationship with environmental factors in Guangdong, China - Yun Zhang; Kun Xin; Baowen Liao; Nong Sheng; Xihang Ai (Ecological Indicators, 2021)
Derris trifoliata, a native plant associated with mangroves, has caused the death of mangrove species in recent years. To explore the pod and seed characteristics in different populations of D. trifoliata, three geographical locations were selected—the cities of Yangjiang (Y), Zhanjiang (Z), and Zhuhai (Qi’ao Island, Q) in Guangdong province—and seven experimental populations Y1, Y2, Y3, Y4, Z1, Z2, and Q1 were selected within these locations. The hundred-grain weight ratio of fresh seed to pod was between 81% and 85% for populations Y1, Y2, Y3, and Y4, and between 67% and 75% for populations Z1, Z2, and Q1. The water content of the seven populations was between 60% and 65%. By using a nested design variance analysis and multiple comparisons, eight phenotypic traits (length, width, thickness, length/width of pod, and seed) were shown to be mainly due to the variance among populations. Principal component analysis based on the eight traits showed a detailed distribution of all individuals among the seven sites, based on the first two principal axes. These results further verified the results of variance analysis which showed differences among populations. The seven populations were divided into four groups based on cluster analysis of the eight traits: population Y1 stood alone, as did Q1; populations Z1 and Z2, and populations Y2, Y3, and Y4 formed two separate groups. Redundancy analysis demonstrated a correlation between environmental factors and populations based on phenotypic traits. The results illustrated that there were differences in the phenotypic traits of pod and seed at different geographical locations and that there were differences in phenotypic traits within the Yangjiang city population. Both pod and seed characteristics were influenced most by TP, SOM, and TN. The results illustrated that D. trifoliata can act as a indicator of mangrove health, human interference and activities need to be reduced and afforestation should be considered in the destroyed areas caused by D. trifoliata.